Elections and Voters in Britain - Denver, David. author. aut Link
XVII, 330 p. 20 illus., 13 illus. in color.
Keywords: How do voters in Britain decide which party to vote for in elections? Have age and education replaced class as the social basis for voting? Are elections now ‘presidentialised’, with voters simply choosing between party leaders? What role do the media, new and old, play in all of this? The authors examine these and other questions in the fourth edition of this popular text. The core of the text is devoted to examining and explaining theories of party choice, including the debate about whether voters are driven more by issues and ideology or by – including the way that and party leaders are now the key determinants of election outcomes – the authors also devote separate chapters to turnout trends and patterns, the media, electoral systems, the geography of party support, and – new to this edition – referendums. Fully revised and with detailed analysis of the 2019 election and the electoral fallout of Brexit, the text incorporates the latest research on elections and voting behaviour, and includes analysis of recent trends and developments – such as the effect of digital media on electoral politics and where recent misfires leave the opinion polls. David Denver is Emeritus Professor of Politics at the University of Lancaster, UK. Rob Johns is Professor of Politics in the Department of Government at the University of Essex, UK.